STRATEGI KOMUNIKASI PEMASARAN KEDAI KOPI KAMAN DALAM MENINGKATKAN LOYALITAS KONSUMEN - Radja Erland Hamzah; Rialdo Rezeky Manogari; Riska Putri Shabrina (FISIP IBI-K57 Prodi Komunikasi, 2020)
The development of the coffee business is currently one of the businesses that are in great demand. The large number of coffee shop businesses cause market competition. This market competition is also experienced by Kedai Kopi Kaman which almost resembles menus at other coffee shops in Depok and the same target consumers. The research methodology uses a qualitative approach to the type of qualitative descriptive research and uses a constructivism paradigm. This research uses data collection techniques through interviews, observation, and literature study. Data analysis techniques with data reduction, data display, and drawing conclusions. The data validity technique is data triangulation. This research uses the concept of PENCILS and Four Step. The results showed that the Kedai Kopi Kaman marketing communication strategy was considered effective and supported by social media, through observation and supporting data which stated that the increase in the number of consumers was quite significant, using word of mouth and Instagram social media.